SAT-199 Diagnostic Dilemma: An Adrenal Incidentaloma in a Young Adult - Sharma, Sonia (J Endocr Soc, 2020)
Introduction: In an adult endocrine clinic, the majority of patients referred for evaluation of an adrenal incidentaloma are older than 30 years of age. It is important to be reminded that a patient may be diagnosed with an adrenal mass at any age but the etiology may vary depending on the age at presentation. Clinical case: An 18 year-old African American female with no significant past medical problems presented with a 2 month history of flank and abdominal pain associated with nausea and vomiting. An abdominal CT scan and a dedicated adrenal CT showed a right adrenal mass measuring 2.2 x 2.6 cm. The noncontrast Hounsfield units were 23, enhanced Hounsfield units 210, and delayed Hounsfield units 72. The calculated washout was 44%, not consistent with an adrenal adenoma. An MRI of the abdomen showed a 2.5 cm right adrenal nodule. The lesion did not demonstrate significant loss of signal between in and out of phase imaging, therefore the characteristics were not consistent with a lipid rich adenoma. Laboratory tests included an ACTH of 31 pg/mL (6-48 pg/mL), cortisol 8.7 ug/mL at 10:57 am (7-9 am 5.27-22.45 ug/mL), aldosterone 10.1 ng/dL (6-48 ng/dL), renin 2.2 ng/mL/hr (upright 0.5-4.0 ng/mL/hr), DHEA-sulfate 129 ug/dL (44-248 ug/dL), plasma free metanephrine 0.10 nmol/L (0.00-0.49 nmol/L), and plasma free normetaneprhine 0.41 nmol/L (0.00-0.89 nmol/L). The 24-hour urine norepinephrine, epinephrine, and metanephrine were all normal, however the 24-hour urine dopamine was elevated, 824 ug/24 hrs (52-480 ug/24 hrs). Subsequently, plasma dopamine, norepinephrine, and epinephrine were all within the reference range. The patient had a robotic-assisted right adrenalectomy removing a 5.7 x 3.5 x 1.7 cm gland, weighing 16.3 grams. The pathology demonstrated a ganglioneuroma within the right adrenal gland measuring 2.2 x 2.0 x 2.7 cm, negative for neuroblastoma or blastic components. Focal hemorrhage was noted, there was no tumor necrosis, and no mitotic figures were present. The tumor appeared to be encapsulated in the adrenal gland and the Ki-67 stain was negative in ganglioneuroma cells. Conclusion: Adrenal adenomas that appear as incidentalomas in young adulthood are extremely rare. Evaluating younger versus older adults found to harbor an adrenal “incidentaloma“ requires a unique approach for each age group, as the differential diagnosis varies widely. In our patient, the imaging was extremely concerning and diagnostic considerations included neuroblastoma, adrenocortical malignancy, pheochromocytoma, or ganglioneuroma. Adrenal ganglioneuromas are most frequently diagnosed in fourth and fifth decades of life. In younger adults ganglioneuromas are usually found in the retroperitoneum and posterior mediastinum. For our patient, surgical resection of the adrenal mass confirmed the pathologic diagnosis and provided definitive cure.